2021
DOI: 10.1029/2021gl092450
|View full text |Cite
|
Sign up to set email alerts
|

Glaciological Monitoring Using the Sun as a Radio Source for Echo Detection

Abstract: While active radio sounding is widely used for both airborne and ground-based surveys (Bell et al., 2011;Jenkins et al., 2006), these measurements are expensive and resource intensive when performed for multiple years, with fine temporal resolution, and on spatial scales greater than several kilometers. However, if radar sounders could perform these measurements without transmitting an electromagnetic pulse for echo detection, this would greatly reduce the power consumption, size, design complexity, and cost o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The Uranian passive sounder concept is based on prior concepts for sounding of Jupiter's Galilean moons using Jovian radio bursts (Romero‐Wolf et al., 2015; Schroeder et al., 2016; Steinbrügge et al., 2021). Passive sounding has been demonstrated experimentally on Earth using reflections of the Sun's quiescent radio emissions reflected off the ocean (Peters et al., 2018), sand (Peters et al., 2021), and water beneath 1 km of ice in Greenland (Peters et al., 2021). Importantly, the authors demonstrated that synthetic aperture radar (SAR) processing was possible in passive radar sounding, enabling additional gain to be recovered (Peters et al., 2021).…”
Section: Concept Overviewmentioning
confidence: 99%
“…The Uranian passive sounder concept is based on prior concepts for sounding of Jupiter's Galilean moons using Jovian radio bursts (Romero‐Wolf et al., 2015; Schroeder et al., 2016; Steinbrügge et al., 2021). Passive sounding has been demonstrated experimentally on Earth using reflections of the Sun's quiescent radio emissions reflected off the ocean (Peters et al., 2018), sand (Peters et al., 2021), and water beneath 1 km of ice in Greenland (Peters et al., 2021). Importantly, the authors demonstrated that synthetic aperture radar (SAR) processing was possible in passive radar sounding, enabling additional gain to be recovered (Peters et al., 2021).…”
Section: Concept Overviewmentioning
confidence: 99%
“…The realization and success of these kind of sensor networks will be greatly aided by the experience and innovation involved in creating robust in situ probes currently being deployed beneath and within ice sheets (Prior-Jones and others, 2021). Similarly, the recent development and demonstration of passive radiosounding systems for ranging and imaging (which exploit existing signals of opportunity rather than transmitting their own signal) have the potential to drive down the resource envelope required for both planetary and terrestrial radar sounding sensor networks (Peters and others, 2021). Whether active or passive, muti-or mono-static, in situ radar sounding sensor networks stand to be an increasingly important tool for radioglaciolgy.…”
Section: Future Directions In Technologymentioning
confidence: 99%
“…We hope to raise awareness of which distinctions are still to be made and which are unnecessary and misleading. However, this letter is focused solely on active radar systems; passive radar sounders such as those used by Peters and others (2021) and Howat and others (2018) are not considered in the following.…”
Section: Variety Of Radar Terminologies and Principlesmentioning
confidence: 99%